PENGGUNAAN COMPUTED RADIOGRAPHY UNTUK IDENTIFIKASI MADU LEBAH - MAIYENA, SRI (IAIN Batusangkar, 2016)
Research on identification of honey bee using Computed Radiography has been done. The testing was carried out by providing digital radiograph of the three types of honey bee. The voltage of the x-ray generator was varied at 50 kV, 60 kV and 70 kV, while filament current was set at 100 mA and exposure time was at 5 ms. Honey bee was identified based on the image line profile that indicated the distribution of linear absorption coefficient (µ) for each sample. The analyses on the image line profile showed that at the voltage of 50 kV and 70 kV the three kinds of the honey bee can be distinguished. However, at the voltage of 60 kV the difference among honey bee was unable to be identified.